Hubungan Efikasi Diri Pengambilan Keputusan Karier dan Pengambilan Keputusan Karier pada Siswa SMA - Adhi Darmasaputro; William Gunawan (JURNAL PSIKOLOGI, 2018)
Abstract This study aimed to determine the correlation of career decision-making self-efficacy and career decision making. The hypothesis of this study that there is a correlation between self-efficacy and career decision making. Subjects in this study are 405 high school students in Jakarta. This study used quantitative research methods and data collection using CDSE-SF (Career Decision Self Efficacy- Short Form) and CDS (Career Decision Scale) which has been translated into Indonesian. The result of the reliability test for CDSE-SF scale was 0.840 and 0.866 for CDS scale. The result validity test of CDSE-SF from 0.310 to 0.551; while CDS of 0.334 to 0.641. The process of data analysis using SPSS 17 applications, Pearson product moment correlation. These results contrast with the hypothesis, there was no correlation between career decision making self-efficacy and career decision making (r = 0.094, p> 0.05). It can be concluded that the proposed hypothesis is rejected. This study has contributed in the field of educational psychology research additions adolescent career.Keywords: career decision-making self-efficacy, career decision making